2020
DOI: 10.1186/s12888-020-02806-7
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ multi-layered expectations when requesting an Autism Spectrum Disorder assessment of their young child: an in-depth interview study

Abstract: Background Parents are valued stakeholders in research, clinical practice and policy development concerning autism spectrum disorder (ASD). However, little is known about what drives and moves parents besides their obvious worries and help request when they ask for a diagnostic ASD assessment of their child. Methods Seventeen Flemish parents of 11 young children participated in a longitudinal study consisting of three in-depth interviews before and after their child’s diagnostic ASD assessment. Data were ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Consistent with previous research (Kiami & Goodgold, 2017; Pepperell et al, 2018), this study found that parents used more active strategies to cope with an ASD diagnosis, with trying to find the positive side being the most typically used strategy. For many parents undergoing the diagnostic process, the primary concern is a diagnosis, wishing to understand and gain certainty about what is going on with their children (Jacobs et al, 2020a). During the postdiagnosis period, parents who have resolved reactions to the diagnosis can adapt to their child's condition, understand the demands placed on their parenthood and perceive positive aspects of ASD (Reed & Osborne, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous research (Kiami & Goodgold, 2017; Pepperell et al, 2018), this study found that parents used more active strategies to cope with an ASD diagnosis, with trying to find the positive side being the most typically used strategy. For many parents undergoing the diagnostic process, the primary concern is a diagnosis, wishing to understand and gain certainty about what is going on with their children (Jacobs et al, 2020a). During the postdiagnosis period, parents who have resolved reactions to the diagnosis can adapt to their child's condition, understand the demands placed on their parenthood and perceive positive aspects of ASD (Reed & Osborne, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Such complexity has not inhibited substantial advancements in this field. On the contrary, the critical need for increased awareness, comprehensive screening, and early intervention is a recurrent theme in the literature, driving significant progress in the field [5][6][7][8][9]. Research has consistently demonstrated that early detection can profoundly reduce distress, preserve cognitive function, and enhance the quality of life and independence for individuals with ASD who engage in intervention programs.…”
Section: Impact On Families and Heterogeneity Of Asdmentioning
confidence: 99%